Use of Fly Ash in Combination with Bauxite Residue in Sustainable Concrete Manufacture - Wahyuni, A.; Nikraz, Hamid (Nova Science Publications Inc., 2014)
This chapter presents the application of fly ash as a partial replacement of cement together with the use of red sand (bauxite residue) as fine aggregate in concrete manufacture. The experimental results of 5 types of concrete e.g.: control mix, concrete incorporating red sand with 0%, 10% and 30% fly ash, and the second control mix with 10% fly ash are used to study the combined effect of fly ash and red sand on various properties of concrete. These concrete mixtures are compared in terms of mechanical properties and durability by applying the following generic tests: compressive strength, splitting tensile strength, flexural strength, modulus of elasticity, water permeability, and chloride diffusion. The pH dependence leaching test was applied only to the concrete specimen that achieved the highest strength. The concrete strength is not shown to be significantly affected when the fine aggregate of natural sand is replaced completely with red sand. The fly ash addition seems to effect in a positive way to improve the workability and durability of concrete. The leaching test results did not exceed the guidelines given by NSW EPA.